An Analysis of Automated Guided Vehicle Standards to Inform the Development of Mobile Orchard Robots. Issue 16 (2016) - Bell, Jamie; MacDonald, Bruce A.; Ahn, Ho Seok; Scarfe, Alistair J.
Abstract: This paper aims to leverage knowledge and experience, gained from the well-established Automated Guided Vehicle (AGV) industry, to highlight key hazards and solutions that may be considered in the risk assessment and risk reduction of large autonomous mobile service robots in orchards. There are notable differences between orchard environments and the warehouses or factories, where AGVs operate, including the presence of uncontrolled growth, exposure to the weather as well as the slope, softness, cluttered and undulating nature of terrain in orchards. However, there are also many similarities in the technologies used, the basic navigation tasks that have to be performed and the nature of the hazards that arise. This paper discusses these similarities and differences in relation to key parts of AGV standards, EN 1525:1997 and ANSI/ITSDF B56.5-2012.